2021
DOI: 10.1038/s41598-021-88436-9
|View full text |Cite
|
Sign up to set email alerts
|

GABA enhancement by simple carbohydrates in yoghurt fermented using novel, self-cloned Lactobacillus plantarum Taj-Apis362 and metabolomics profiling

Abstract: This study aimed to enhance natural gamma aminobutyric acid (GABA) production in yoghurt by the addition of simple sugars and commercial prebiotics without the need for pyridoxal 5′-phosphate (PLP) cofactor. The simple sugars induced more GABA production (42.83–58.56 mg/100 g) compared to the prebiotics (34.19–40.51 mg/100 g), with glucose promoting the most GABA production in yoghurt (58.56 mg/100 g) surpassing the control sample with added PLP (48.01 mg/100 g). The yoghurt prepared with glucose also had the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Nonetheless, the amounts of bioaccesible GABA at the end of intestinal digestion were greater for BrKC as compared to BrWF. Resistance of GABA to the gastric environment (pH 1.2) and intestinal conditions was also reported earlier during simulated gastrointestinal digestion of a GABA-rich yogurt in agreement with our results [ 39 , 40 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Nonetheless, the amounts of bioaccesible GABA at the end of intestinal digestion were greater for BrKC as compared to BrWF. Resistance of GABA to the gastric environment (pH 1.2) and intestinal conditions was also reported earlier during simulated gastrointestinal digestion of a GABA-rich yogurt in agreement with our results [ 39 , 40 ].…”
Section: Resultssupporting
confidence: 93%
“…Regular dietary intake of polyphenols, approximately 1–2 g per day, has been associated with chronic disease prevention [ 39 ]. Although there are no official recommendations for phenolic compounds, it is worth noting that a serving of 50 g of the developed BrKC could cover almost 25% of the reported mean daily intake (1 and 1.2 g/d) [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the amounts of bioaccessible GABA at the end of intestinal digestion were greater for BQC as compared to the control. The resistance of GABA to the gastric environment (pH 1.2) and intestinal conditions was also reported during the simulated gastrointestinal digestion of a GABA-rich yoghurt [ 56 ]. In another study, Dala-Paula et al [ 57 ] indicated that GABA content increased after the in vitro digestion of chocolate due to digestive enzymes, which agreed with our results.…”
Section: Resultsmentioning
confidence: 99%
“…lactis 017 from isolated cheese produced 2700 mg L −1 GABA in skimmed milk. Hussin et al (2021) stated that GABA values varied from 42.83 to 58.56 mg 100 g −1 in yogurt with simple sugars (glucose, sucrose, fructose), and from 34.19 to 40.51 mg 100 g −1 yogurt with prebiotics (inulin, FOS, GOS), whereas the GABA value was determined as being 48.01 mg 100 g −1 in yogurt with added pyridoxal 5′‐phosphate (control). GABA in fermented products has been formed by starter microorganisms such as Lb.…”
Section: Resultsmentioning
confidence: 99%